Method and Critical Aspect of Semisolid Mixing (Sciences of Pharmacy, 2022)
Semisolid preparations are widely used to deliver drugs through the skin, cornea, rectal tissue, nasal mucosa, vagina, buccal tissue, urethral membrane, and outer ear lining. They can prevent the first-pass metabolism, reduce side effects, provide immediate local effects, and increase patient compliance. However, an improper manufacturing process will produce a system with bad characteristics, one of which is the mixing process. Several conditions that need to be considered, such as vacuum, temperature, humidity, pressure, stirring speed, stirring time, shear stress, the volume of the mixture, and type of impeller, can affect the consistency, size, and dispersion of particle size, homogeneity, porosity, reactivity, and other characteristics that affect the quality of the semisolid system. Therefore, this article discusses the critical aspects of semisolid mixing, the types, principles, and specifications of several mixer tools and impellers, and how they affect the characteristics of semisolid systems. This review concludes that each type of semisolid preparation requires an impeller and mixer with the specifications and mixing conditions that suit the needs in maintaining the stability and quality of the semisolid system.